Workbook for English Drama by Incorporating Character Building for College Students - Yulieda Hermaniar (Universitas Negeri Malang, 2015)
Abstract: Drama class in its relation to education gives mental and intellectual experience in mastering English as language and culture. As an authentic material, drama class in university level should explore students' competence by providing varied material and activities. The development of a workbook by incorporating character building aspects for drama class in Lambung Mangkurat University is seen important. The workbook is developed by following the result of need assessment and the demand of course competenceof English Department in Lambung Mangkurat University. By involving 20 students of drama class, the research is carried out by following the modified stage of development by Borg and Gall. The result of the development shows that the developed workbook can be categorized as good product from the result of quantitative data in all aspects. Therefore, the workbook can be used as one of the component in teaching in the drama class. Key Words: workbook, english drama, character building   Abstrak: Kelas drama terkait dengan pendidikan memberikan pengalaman mental intelektual dalam penguasaan bahasa Inggris dari aspek kebahasaan dan budaya. Sebagai sumber otentik, kelas drama di universitas hendaknya menggali kemampuan siswa dengan memberikan ragam materi dan aktivitas. Pengembangan buku kerja dengan menggabungkan unsur pendidikan karakter bagi mahasiswa kelas drama Inggris di Jurusan Pendidikan Bahasa Inggris di Universitas Lambung Mangkurat (UNLAM) adalah penting. Buku kerja ini dikembangkan berdasarkan kebutuhan siswa dan disesuaikan dengan tuntutan pokok bahasan pada kelas drama di Jurusan Pendidikan Bahasa Inggris di UNLAM. Dengan melibatkan 20 siswa kelas Drama di program studi Bahasa Inggris FKIP UNLAM, penelitian pengembangan dilakukan dengan mengikuti tahapan modifikasi dari Borg & Gall. Hasil penelitian menunjukkan buku kerja yang dikembangkan dikatagorikan baik berdasarkan hasil data kuantitatif dari semua aspek. Buku kerja ini dapat dijadikan pelengkap komponen dalam pengajaran di kelas Drama. Kata kunci: buku kerja, drama bahasa Inggris, pendidikan karakter